Assessment of Thermal Comfort in Bus Station: A Case Study of Bentayan Bus Station, Muar - Haizat Kuzairi Roslee,; Nurul Hidayah Roslan, (Progress in Engineering Application and Technology, 2025)
Public transportation facilities play a crucial role in urban mobility, offering convenience and sustainability. Ensuring thermal comfort within these facilities significantly impacts passenger satisfaction, well being, and overall user experience. The Bentayan Bus Station in Muar, Johor, serves as a key transit hub but faces challenges in maintaining optimal thermal comfort levels, particularly in the waiting area, due to inadequate ventilation, excessive solar heat gain, and insufficient shading devices. This study assessed thermal comfort performance through on-site measurements of air temperature averaging 30.5°C, air velocity varied from 0.1 m/s to 1.5 m/s, and peak percentage for relative humidity 84%, using the LSI LASTEM Heatshield device. Passenger perceptions were collected via structured questionnaires from 101 respondents to gauge their comfort levels and overall experience. Data analysis aligned with ASHRAE Standard 55 revealed Predicted Mean Vote (PMV) values of 2.3 and Predicted Percentage Dissatisfied (PPD) at 84.1%, indicating significant thermal discomfort. Survey feedback highlighted the need for better air circulation and improvements to cooling systems and ventilation. The findings emphasize the necessity for interventions such as advanced mechanical ventilation systems, passive cooling techniques, and the integration of shading solutions to reduce solar heat gain. These measures are vital for enhancing user satisfaction, aligning the station’s thermal environment with international standards, and supporting sustainable urban transit development. Overall, this research underscores the importance of thermal comfort in public transportation facilities to improve the passenger experience and operational efficiency